Persepsi Wisatawan Danau Toba Tentang Wisata Mistis - Rahul Paisal Siadari; Dyva Claretta (Universitas 45 Surabaya, 2023)
This research is motivated by the existence of a mystical tourism development plan launched by Sandiaga Uno with the aim of increasing state revenue from the tourism sector and increasing new jobs and existing businesses in the development area. Because Lake Toba has been included in the super priority development, This study aims to determine how the perception of Lake Toba tourists to the planning of mystical tourism development in Lake Toba as their destination of choice. In knowing perception, the researcher uses Alex Sobur's theory of perception which is used to find out how the meaning is in tourists. The research method used is descriptive qualitative method, to describe how the perceptions were found in more detail. The data in this study were obtained through in-depth interviews and documentation obtained from existing informants. This study obtained results showing that Lake Toba tourists' perceptions of the planning of mystical tourism development are as a form of effort in preserving culture, local wisdom values, and traditions that exist in the Batak community in Lake Toba as well as being a means of learning life for tourists whose stories in it can be taken as evaluate how to think and act properly, and as a means to introduce culture, traditions, customs to tourists.